Sampling Recently Arrived Immigrants in the UK: Exploring the effectiveness of Respondent Driven Sampling - Tom Frere-Smith; Renee Luthra; Lucinda Platt (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Surveying recently arrived immigrants in countries lacking a population register poses many challenges. We describe our adaptation of Respondent Driven Sampling, a chain-referral technique, to sample migrants from Pakistan and Poland who had arrived in the UK within the previous 18 months. Specifically, we discuss issues around connectedness, privacy, clustering, and motivation, central to the implementation of RDS. We outline techniques adopted and evaluate their success. We conclude that RDS is unlikely to be suitable for accessing newly arrived migrants. However, in the absence of registers which can capture populations at point of entry there are no obvious alternatives.
Keywords: F22; J15; 330; new immigrants; surveys; RDS; immigrant networks; integration; non-response